Дослідження на передгородді в Чернігові у 2022 р. - Моця, О.П.; Скороход, В.М.; Жигола, В.С.; Ситий, Ю.М. (Археологія, 2023)
Представлено результати розкопок на території літописного Передгороддя Чернігова, під час яких було
досліджено житлово-господарську забудову ХІ—
ХІІІ ст., курганний та ґрунтовий могильники кінця
Х—ХІІІ ст. New archeological research was conducted in the Suburbs of Chernihiv in 2022. It was 150 m to the west from the defensive line
of the Okolny Grad and this made it possible to study this part of the city and trace its development in different chronological
horizons.
At the end of the 10th — at the beginning of the 11th centuries this place was used as a barrow and soil burial ground. At the
end of the 11th century there emerged manor buildings directly near the fortifications, which could have been destroyed in 1094.
At this time three residential buildings were registered. The boundaries of estates in the shape of ditches from fences appeared at
this stage and had the same borders for all time periods.
In the first half of the 12th century new buildings were erected, which could also have been destroyed in the fire in 1152. A clay
oven was discovered in one of the houses, where the plinth was used as a structural element during its construction. Fragments of
the plinth were also found in other buildings. The parameters of such a plinth are similar to the plinth of the Illinska Church on
the Boldyni Hory near the entrance to the caves. A similar plinth is found in the masonry of the Saints Borys and Hlib Cathedral.
In the second half of the 12th — the first half of the 13th centuries increased the number of houses and household building.
At one of them a processed elk horns were found, that can indicate a bone-cutting workshop. During all chronological periods
manor buildings were fixed, but houses, household buildings and fences were always oriented by walls on the sides of the world.
Constructions of the first half of the 13th century could have disappeared as a result of a fire during military operations in 1234—
1235 or after the Mongol invasion.
After the cessation of life in this part of the city, a cemetery appeared on the territory of the former estates, the burials of
which were arranged in the pits of houses of the first half of the 13th century. The cemetery could function even after the Mongol
invasion. The density of buildings and the presence of burials from different time periods attest to the intensive use of this part
of the Suburbs of Chernihiv during Old Rus period.